Shake table tests on deficient RC buildings strengthened using post-tensioned metal straps - Garcia, Reyes; Hajirasouliha, Iman; Pilakoutas, Kypros; Helal, Yasser; Jemaa, Yaser; Guadagnini, Maurizio; Petkovski, Mihail; Mongabure, Philippe; Anca Ciupala, Mihaela; Kyriakides, Nicholas; Chrysostomou, Christis; Ilki, Alper; et al. (My University, 2014)
The European research project BANDIT investigated the effectiveness of a novel Post-Tensioned Metal Strapping (PTMS) strengthening technique at improving the seismic performance of deficient RC buildings using shake table tests. A full-scale two-story structure was designed with inadequate reinforcement detailing of columns and beam-column joints so as to simulate typical deficient buildings in Mediterranean and developing countries. Initial shaking table tests were carried out until significant damage was observed in the beam-column joints.
Keywords: Post-Tensioned Metal Strapping; Mediterranean and developing countries; table tests